Feasibility of tau g-2 measurements in ultra-peripheral collisions of heavy ions - Nazar Burmasov, Evgeny Kryshen, Paul Buehler, Roman Lavicka (SciPost Physics Proceedings, 2025)
The anomalous magnetic moment of the tau lepton, $a_τ=(g_τ - 2)/2$, is a sensitive probe of new physics but is extremely difficult to measure precisely in contrast to electron and muon moments. The best experimental limits were set by the DELPHI collaboration more than 15 years ago in studies of the ditau production in the $ee→ eeττ$ process. Ultra-peripheral collisions (UPCs) of heavy ions at the LHC may provide a unique opportunity to improve the $a_τ$ constraints in the studies of ${\rm Pb + Pb}→ {\rm Pb + Pb}+ττ$ process. We review recent proposals to study ditau production via semi-leptonic tau decays in Pb-Pb UPC with the available ATLAS and CMS data and discuss the feasibility to explore this process down to low transverse momenta of decay leptons with the ALICE and LHCb experiments.